Avaliação da reação tecidual de uma resina termoplástica em tecido subcutâneo de ratos - Alfenas, Elizabeth Rodrigues [UNESP] (1995)
Subcutaneous rat tissue reaction was evaluated using samples of a thermoplastic resin(TAK Hydroplastic-DFL) of different colours: pink, yellow, blue and white. As control, a transparent thermally activated acrylic resin was used. Samples with a diameter of approximately 8 mm and thickness of 1 mm were implanted in surgical wounds on the back of rats, which were then sacrificed at periods of 2, 3, 6, and 12 weeks. The adjacent tissue was removed and prepared histologically using hematoxilin-eosin and Mallory trichrorne techniques. Through optical microscopy, it was observed that the subcutaneous adjacent to the resin implants showed a moderate inflammatory reaction during the weeks 2 and 3. At the end of week 12, tissue recovery and capsular formation surrounding the resin implant were observed. It was concluded that: • the thermoplastic resin in pink, yellow, b1ue and white colours didn't determine unfavourable tissue reaction in the 12 weeks of implantation; • the resin of the control group and the blue thermoplastic resin determined a tissue response that was less favourable than the thermoplastic resin in pink, yellow and white colours